Mothers’ experiences as legal guardian of children's phlebitis during hospitalization in Indonesia: A phenomenological study - Casman, Casman; Mahanani, Dian; Wawo, Balbina Antonelda Marled; Iqbal, Muhammad; Ariani, Desy Rizki; Pradana, Anung Ahadi (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Peripheral intravenous catheter (PIVC) insertion is a common procedure performed by nurses for hospitalized children, but phlebitis—an inflammation of the vein—is a frequent complication. The response of the mother, as the child’s primary caregiver, plays a key role in the healing process when phlebitis occurs. Objective: This study aimed to explore mothers’ experiences and perceptions regarding the occurrence and management of phlebitis in their children during hospitalization. Methods: A descriptive phenomenological design was employed for this study, conducted between August and October 2023. Semi-structured interviews were conducted with sixteen mothers whose children had experienced phlebitis during their hospital stay. The interviews were transcribed verbatim, and data were analyzed using content analysis. Each participant validated the transcripts before analysis. Results: Three main themes emerged from the data: 1) Risk factors and causes of phlebitis; 2) Early detection and confirmation of phlebitis; and 3) Management of IV infusion occlusions. Conclusion: Although the causes and risk factors for phlebitis in children cannot be entirely avoided, early detection by mothers can reduce some risks. The study also identified gaps in nursing practice, particularly regarding the management of infusion occlusions, with some practices deviating from standard procedures. To improve outcomes, nurses should adhere to evidence-based protocols for maintaining IV patency and proactively educate mothers on recognizing signs of phlebitis. Strengthening nurse-mother communication and ensuring consistent implementation of best practices are essential for preventing and effectively managing phlebitis in pediatric patients.